Synaptic Plasticity and Learning in Animal Models of Tuberous Sclerosis Complex. (15th July 2012) - Kirschstein, Timo
Abstract : Tuberous sclerosis complex (TSC) is caused by a mutation of either the Tsc1 or Tsc2 gene. As these genes work in concert to negatively regulate the mammalian target of rapamycin (mTOR) kinase which is involved in protein translation, mutations of these genes lead to a disinhibited mTOR activity. Both the clinical appearance of this condition including tumors, cognitive decline, and epileptic seizures and the molecular understanding of the mTOR signaling pathway, not only involved in cell growth, but also in neuronal functioning, have inspired numerous studies on learning behavior as well as on synaptic plasticity which is the key molecular mechanism of information storage in the brain. A couple of interesting animal models have been established, and the data obtained in these animals will be discussed. A special focus will be laid on differences among these models, which may be in part due to different background strains, but also may indicate pathophysiological variation in different mutations.